Single Small Molecule‐Assembled Mitochondria Targeting Nanofibers for Enhanced Photodynamic Cancer Therapy In Vivo. (16th December 2020) - Lin, Kai; Ma, Zhao; Li, Jin; Tang, Menghuan; Lindstrom, Aaron; Ramachandran, Mythili; Zhu, Shaoming; Lin, Tzu‐yin; Zhang, Lanwei; Li, Yuanpei
Abstract: Photodynamic therapy (PDT) has emerged as an attractive alternative in cancer therapy, but its therapeutic effects are limited by the nonselective subcellular localization and poor intratumoral retention of small‐molecule photosensitizes. Here a fiber‐forming nanophotosensitizer (PQC NF) that is composed of mitochondria targeting small molecules of amphiphilicity is reported. Harnessing the specific mitochondria targeting, the light‐activated PQC NFs produce approximately 110‐fold higher amount of reactive oxygen species in cells than free photosensitizers and can dramatically induce mitochondrial disruption to trigger intense apoptosis, showing 20–50 times better in vitro anticancer potency than traditional photosensitizers. As fiber‐shaped nanomaterials, PQC NFs also demonstrated a long‐term retention in tumor sites, solving the challenge of rapid clearance of small‐molecule photosensitizers from tumors. With these advantages, PQC NFs achieve a 100% complete cure rate in both subcutaneous and orthotopic oral cancer models with the administration of only a single dose. This type of single small molecule‐assembled mitochondria targeting nanofibers offers an advantageous strategy to improve the in vivo therapeutic effects of conventional PDT. Abstract : An amiphiphilic photosensitizer‐derived small molecule that can self‐assemble into a fiber‐forming nanoconstruct is developed. The one‐component nanofiber not only exhibits significant phototoxicity to cancer cells through targeting mitochondria, but also shows long‐term retention at the tumor site, thus achieving a 100% complete cure rate in both subcutaneous and orthotopic oral cancer models with only a single‐dose administration.